Re-vitalizing money demand in the euro area: Still valid at the zero lower bound - Christian Dreger; Dieter Gerdesmeier; Barbara Roffia (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
The analysis of monetary developments have always been a cornerstone of the ECB's monetaryanalysis and, thus, of its overall monetary policy strategy. In this respect, money demandmodels provide a framework for explaining monetary developments and assessing price stabilityover the medium term. It is a well-documented fact in the literature that, when interestrates are at the zero lower bound, the analysis of money stocks become even more importantfor monetary policy. Therefore, this paper re-investigates the stability properties of M3 demandin the euro area in the light of the recent economic crisis. A cointegration analysis isperformed over the sample period 1983 Q1 and 2015 Q1 and leads to a well-identified modelcomprising real money balances, income, the long term interest rate and the own rate of M3holdings. The specification appears to be robust against the Lucas critique of a policy dependentparameter regime, in the sense that no signs of breaks can be found when interest ratesreach the zero lower bound. Furthermore, deviations of M3 from its equilibrium level do notpoint to substantial inflation pressure at the end of the sample. Excess liquidity models turnout to outperform the autoregressive benchmark, as they deliver more accurate CPI inflationforecasts, especially at the longer horizons. The inclusion of unconventional monetary policymeasures does not contradict these findings.
Keywords: E41; E44; E52; G11; G15; 330; Euro area money demand; inflation forecasts; unconventional monetary policy